2017
DOI: 10.1038/nature24454
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics reconstructs fate conversion from fibroblast to cardiomyocyte

Abstract: Summary Direct lineage conversion offers a new strategy for tissue regeneration and disease modeling. Despite recent success in directly reprogramming fibroblasts into various cell types, the precise changes that occur as fibroblasts progressively convert to target cell fates remain unclear. The inherent heterogeneity and asynchronous nature of the reprogramming process renders it difficult to study using bulk genomic techniques. Here, to overcome this limitation, we applied single-cell RNA-seq to analyze glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
168
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(177 citation statements)
references
References 43 publications
7
168
2
Order By: Relevance
“…Epicardial cells were detected based on expression of genes such as Lrrn4 and Mgp (cluster 12, Figure 1E) (Xiao et al, 2018). Notably, the expression of these genes exclusively within endocardium and epicardium cells throughout our time course does not support a previous report that suggested these genes are expressed at early stages in reprogramming cells but subsequently repressed by GMT expression (Figure 1C-D) (Liu et al, 2017). Instead, our analysis suggests these distinct cell types persist in the population in low numbers and were not detected in the previous study due to a limitation in the number of cells captured.…”
Section: Multiple Transcription Signatures Identified During Cardiac contrasting
confidence: 69%
See 1 more Smart Citation
“…Epicardial cells were detected based on expression of genes such as Lrrn4 and Mgp (cluster 12, Figure 1E) (Xiao et al, 2018). Notably, the expression of these genes exclusively within endocardium and epicardium cells throughout our time course does not support a previous report that suggested these genes are expressed at early stages in reprogramming cells but subsequently repressed by GMT expression (Figure 1C-D) (Liu et al, 2017). Instead, our analysis suggests these distinct cell types persist in the population in low numbers and were not detected in the previous study due to a limitation in the number of cells captured.…”
Section: Multiple Transcription Signatures Identified During Cardiac contrasting
confidence: 69%
“…Direct reprogramming of cardiac fibroblasts to cardiomyocytes has been achieved by ectopic expression of cardiac-enriched factors Ieda et al, 2010;Nam et al, 2013;Qian et al, 2012;Song et al, 2012). Ectopic expression of Gata4, Mef2c, and Tbx5 (GMT) is sufficient to alter the fibroblast epigenome and promote expression of genes associated with cardiomyocytes while simultaneously repressing the fibroblast gene program (Ieda et al, 2010;Liu et al, 2017;Zhou et al, 2016). Perturbation of epigenetic remodelers and ectopic expression of additional transcription factors such as Hand2 and MYOCD were found to influence reprogramming as well, with addition of Hand2 resulting in a greater portion of pacemaker-like cells Christoforou et al, 2013;Protze et al, 2012;Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Addition of ZNF281 to the reprogramming cocktail suppressed the expression of genes associated with the inflammatory response and modulated cardiac gene expression by interacting with the transcription factor GATA4 (REF 123 ). In other studies, suppressing the expression of genes encoding certain factors such as the Polycomb complex protein BMI1 and the splicing factor polypyrimidine tract-binding protein 1 (PTB) enhanced cardiac reprogramming, suggesting that these factors act as barriers to cardiac repro- gramming 124,125 . However, reaching a consensus protocol for in vitro direct reprogramming of fibroblasts into cardiomyocytes is difficult because in these studies the cardiomyocyte markers, source of fibroblasts, and the time of analysis differ.…”
Section: Direct Reprogramming For Heart Repairmentioning
confidence: 99%
“…Intriguingly, GMT (Gata4, Mef2c, Tbx5)-driven CF-to-CM trans-differentiation requires downregulation of almost completely overlapped members of ARSs 37 as found in CF-tomyofibroblast transition, including the same nine ARSs plus LARS, RARS, and KARS. The GO analysis in this report 37 has shown that ARS and ECM gene pathways are among the top enriched in a gene cluster that is unaltered in gene expression during CM-to-pre-iCM transition and drops during pre-iCM-to-iCM maturation. Among all altered ARSs, EPRS is dramatically reduced during this process, thereby possibly contributing to the silencing of collagen expression during CF-to-CM conversion.…”
Section: Discussionmentioning
confidence: 70%